Cupcake fix - Fang, Vicky (Fang, Vicky. Layla and the Bots, 2021)
Blossom Valley is opening a brand-new community center, and Layla and her Bots are playing at the opening, but the mayor is worried because not many people have signed up to come to the party; so Layla and her bots decide to build a cupcake machine to attract a crowd--but they are uncertain how to manage the variety of decorations proposed. Includes a DIY activity that readers can try at home.